Mochlos IC : period III, neopalatial settlement on the coast, the artisans' quarter and the farmhouse at Chalinomouri : the small finds (Prehistory monographs, 2004)
List of Tables; List of Figures; List of Plates; Acknowledgments; Abbreviations; Introduction; 1 The Mochlos Ship Cup; 2 Ceramic, Stone, Bone, and Shell Objects; 3The Metal Finds and theirGeological Sources; 4The Stone Implements; 5 Minerals and Rocks; 6Fauna and Flora; 7Conclusions; Appendix A; Appendix B; Bibliography; Concordance A; Concordance B; Index.